Interleukin‐33 (IL‐33): A nuclear cytokine from the IL‐1 family. Issue 1 (16th December 2017) - Cayrol, Corinne; Girard, Jean‐Philippe
Summary: Interleukin‐33 (IL‐33) is a tissue‐derived nuclear cytokine from the IL‐1 family abundantly expressed in endothelial cells, epithelial cells and fibroblast‐like cells, both during homeostasis and inflammation. It functions as an alarm signal (alarmin) released upon cell injury or tissue damage to alert immune cells expressing the ST2 receptor (IL‐1RL1). The major targets of IL‐33 in vivo are tissue‐resident immune cells such as mast cells, group 2 innate lymphoid cells (ILC2s) and regulatory T cells (Tregs). Other cellular targets include T helper 2 (Th2) cells, eosinophils, basophils, dendritic cells, Th1 cells, CD8 + T cells, NK cells, iNKT cells, B cells, neutrophils and macrophages. IL‐33 is thus emerging as a crucial immune modulator with pleiotropic activities in type‐2, type‐1 and regulatory immune responses, and important roles in allergic, fibrotic, infectious, and chronic inflammatory diseases. The critical function of IL‐33/ST2 signaling in allergic inflammation is illustrated by the fact that IL33 and IL1RL1 are among the most highly replicated susceptibility loci for asthma. In this review, we highlight 15 years of discoveries on IL‐33 protein, including its molecular characteristics, nuclear localization, bioactive forms, cellular sources, mechanisms of release and regulation by proteases. Importantly, we emphasize data that have been validated using IL‐33 ‐deficient cells.